Total asset management in the public client: a critical analysis of building maintenance budget determination / Norehan @ Norlida Mohd Noor and Md Yusof Hamid - Mohd Noor, Norehan; Hamid, Md Yusof (Universiti Teknologi MARA, Perak, 2011)
This paper draws on an exploratory study of determination of the maintenance budget of the government-owned buildings. Today's situation witnesses drastic developments in government policy direction with the establishment of a strategic and effective asset management. The Government's main focus is to establish a robust guideline in determining budget allocations for maintenance of government building projects. The purpose of this study is to investigate the current and various practices used in the management of the maintenance budget determination by the Government of Malaysia in particular by the Public Works Department or the local authorities and the challenges faced by the maintenance contractors in the project.